FRI0340 Breastfeeding in Systemic Lupus Erithematosus. (15th July 2016) - Acevedo, M.; Pretini, J.; Micelli, M.; Sequeira, G.; Kerzberg, E.M.
Abstract : Background: Breastfeeding is the optimal source of nourishment for newborns and infants during their first year of life.Both short and long benefits accrue to mothers who breastfeed (1, 2). The clinical condition of patients with systemic lupus erythematosus (SLE) may have an impact on breastfeeding onset and duration. Objectives: Assess breastfeeding in patients with SLE. Methods: Retrospective case-control study. Patients who had got pregnant after being diagnosed with SLE (4 or more SLICC ACR/EULAR criteria) and whose pregnancies had been followed up in the hospital were interviewed. The control group consisted of patients approached in the waiting-room of the paediatrics service. The data collected included epidemiological information, main features of their pregnancies and newborns, breastfeeding duration, and reasons for weaning. This study was approved by the Bioethics Committee of the Ramos Mejia Hospital, and both patients and controls signed the informed consent form. Results: Thirty-six pregnancies in 31 patients with SLE and the same number of controls were studied. The following features were similar in both groups: current age, age at the time of delivery, level of education, average number of children, number of patients that breastfed for the first time, and preterm birth rates. Patients with SLE had planned their pregnancies ahead less frequently than controls (16.7% vs 44.4%, p 0.02), they had experienced a greater number of complications during the pregnancies (33.6% vs 5.6%; p 0.007), and their newborns showed a higher trend to minor complications (25% vs 11.1%; p 0.2). Twenty-five percent of the patients with SLE presented some kind of complication during puerperium, mainly related to disease activity, versus none in the controls (p 0.001). Also, a higher number of patients with SLE did not even initiate breastfeeding (19.4% vs 5.6% in the controls; p 0.07). Breastfeeding average duration in patients with SLE was 6 months (SD 6 months) versus 12 months (SD 8 months) in the controls (Log Rank p: 0.003). Fifty-two percent of the controls mentioned that there had been no reason for weaning and considered that they had nursed their children a suitable amount of time. Conversely, patients with SLE frequently set weaning in motion on the grounds that they had been placed on medication (42%). However, when the medication was analysed, in 6 of 11 cases (55%), it consisted of low doses of corticoids or Hydroxychloroquine. Conclusions: In this retrospective case-control study it was observed that patients with SLE show a lower trend to initiate breastfeeding, and they sustain it for less time than controls (6 months vs 12 months respectively). Although the most common reason for weaning is the administration of medication, breastfeeding duration could be optimised by improving the level of information provided to patients. References: American Academy of Pediatrics. Section on breastfeeding: policy statement: breastfeeding and the use of human milk. Pediatrics 2012; 129: e827–41. World Health Organization. Breastfeeding health topic. Available at http://www.who.int/topics/breastfeeding/es [accessed on 15 January 2016]. Acknowledgement: Prof. Ana Insausti. Disclosure of Interest: None declared